New aspects of anticoagulant therapy in atrial fibrillation in patients with renal dysfunction - Zh. D. Kobalava; P. V. Lazarev; M. V. Vatsik (Российский кардиологический журнал)
Atrial fibrillation (AF) and chronic kidney disease (CKD) are common and interrelated diseases, the combination of which is associated with a poor prognosis. The efficacy and safety of direct oral anticoagulants (DOACs) used to prevent thromboembolic complications of AF may depend on renal function due to the specific pharmacokinetics of these drugs. This review considers current data on the role of kidneys in the pathogenesis of ischemic and bleeding events, methods of renal function assessment and related classification issues, as well as comparison of warfarin and DOAC therapy, in patients with AF and renal dysfunction of different stages based on the results of randomized controlled trials and actual clinical practice. DOAC use in the context of dynamic deterioration of renal function, supranormal renal function, and their effect on renal outcomes is discussed. International guidelines on anticoagulant therapy in AF and renal dysfunction were analyzed.